The Human Right to Water and Sanitation: Going Beyond Corporate Social Responsibility - Aguilar Cavallo, Gonzalo (Utrecht Journal of International and European Law, 2013)
Traditionally, it has been understood that private corporations cannot be held responsible for human rights violations at the international level. Only States, main subjects of public international law, can be held legally responsible for human rights violations. Today, this classical argument is being increasingly challenged by the force of reality. States remain the entity that is principally responsible for human rights violations, but there is no epistemological reason for denying such responsibility in the case of private corporations at the international level. The increasing number of standards and mechanisms at the regional and international level addressed to enterprises, that enshrine environmental and human rights standards contribute to build this argument. There is a tangible trend that goes beyond corporate social responsibility towards the initial steps of the emergence of international corporate human rights responsibility.